Elevation of Urinary 2‐Hydroxyglutarate in IDH‐Mutant Glioma. (1st February 2016) - Fathi, Amir T.; Nahed, Brian V.; Wander, Seth A.; Iafrate, A. John; Borger, Darrell R.; Hu, Ranliang; Thabet, Ashraf; Cahill, Daniel P.; Perry, Ashley M.; Joseph, Christelle P.; Muzikansky, Alona; Chi, Andrew S.
Abstract : Background: Recurrent mutations in the isocitrate dehydrogenase 1 ( IDH1 ) and IDH2 genes, which are frequent in gliomas, result in marked accumulation of the metabolic by‐product 2‐hydroxyglutarate (2‐HG) within tumors. In other malignancies, such as acute myeloid leukemia, presence of IDH mutation is associated with elevated 2‐HG levels in serum or urine compartments. Circulating 2‐HG in patients with glial malignancies has not been thoroughly investigated. Methods: In this study, we analyzed 2‐HG levels in the serum and urine of a large set of patients with IDH ‐mutant and IDH ‐wild‐type glioma, and the cerebrospinal fluid (CSF) from a subset of this cohort. Results: We found that 2‐HG was elevated in the urine of patients with IDH ‐mutant versus IDH ‐wild‐type glioma, although no significant differences in 2‐HG levels were observed in the serum or the small set of CSF samples obtained. Among patients with IDH ‐mutant glioma, 2‐HG levels did not differ based on the histopathologic grade, genetic subtype ( TP53 mutant or 1p/19q codeleted), presence of a canonical ( IDH1 R132H) or noncanonical (any other IDH variant) mutation, or treatment type. Conclusion: Our finding suggests that urinary 2‐HG is increased among patients with IDH‐mutant gliomas, and may represent a future surrogate, noninvasive biomarker to aid in diagnosis, prognosis, and management. Implications for Practice: Patients with glioma who harbor mutations in isocitrate dehydrogenase genes showed selective elevation of the oncometabolite 2‐hydroxyglutarate in the urine. Similar elevations were not identified in the serum or cerebrospinal fluid. 2‐Hydroxyglutarate may serve as a useful, noninvasive biomarker to stratify patients newly diagnosed with glioma with regard to prognosis and management. Abstract : Isocitrate dehydrogenase ( IDH ) gene mutations, frequent in gliomas, cause increased levels of 2‐hydroxyglutarate (2‐HG). 2‐HG levels were found to be elevated in the urine of patients with IDH ‐mutant versus IDH ‐wild‐type glioma; no significant differences in 2‐HG levels were observed in the serum or the small set of cerebrospinal fluid samples obtained. 2‐HG may represent a future surrogate, noninvasive biomarker to aid in diagnosis, prognosis, and management of IDH ‐mutant glioma.